2017
DOI: 10.4149/bll_2016_136
|View full text |Cite
|
Sign up to set email alerts
|

Fasciotomy closure using negative pressure wound therapy in lower leg compartment syndrome

Abstract: BACKGROUND: Fasciotomy wounds can be a major contributor to length of stay for patients as well as a diffi cult reconstructive challenge. OBJECTIVES: To evaluate lower leg fasciotomy wound closure outcomes comparing treatment with combined dressing fabric (COM) and negative pressure wound therapy (NPWT) in combination with elastic dynamic ligature (EDL). METHODS: Retrospective study of 63 patients who underwent lower leg fasciotomy due to injury treated from January 2008 to December 2015 at the Department of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Negative pressure wound therapy creates a closed environment that protects the wound from the external environment. [ 17 ] In addition, VAC is a method that increases wound healing by stimulating angiogenesis and cell division, removing bacteria-rich exudate from wound edges and eliminating edema. [ 18 , 19 ] Kakagia et al[ 15 ] reported infection in 24% of the patients in the VAC group and in 16% of the patients followed with an approximation suture.…”
Section: Discussionmentioning
confidence: 99%
“…Negative pressure wound therapy creates a closed environment that protects the wound from the external environment. [ 17 ] In addition, VAC is a method that increases wound healing by stimulating angiogenesis and cell division, removing bacteria-rich exudate from wound edges and eliminating edema. [ 18 , 19 ] Kakagia et al[ 15 ] reported infection in 24% of the patients in the VAC group and in 16% of the patients followed with an approximation suture.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 28 concluded in his study that VSD associated with skin-stretching device could improve the treatment outcomes of stress-induced injuries. Krticka et al 29 also concluded that VSD combined with a dynamic method could be very effective for fasciotomy wound closure in comparison with traditional techniques. Wu et al 30 and Ji et al 31 shared their successful experience about the application of VSD and skin stretching technique in the treatment of diabetic foot wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of single-incision versus dual-incision fasciotomy shows that the results of applied fasciotomy techniques are similar, and the choice of the method should be based on surgeon experience and clinical patients' condition [11]. Unfortunately, primary wound closure might be difficult to achieve due to significant swelling of the limb, skin retraction and skin edge necrosis [12,13].…”
Section: Discussionmentioning
confidence: 99%